Implementasi Buck-Boost Converter pada Proses Pengereman Regeneratif Motor BLDC - Padilah Hannum Simbolon; Ali Basrah Pulungan (Pusat Pengembangan, Penelitian dan Pengabdian kepada Masyarat (P4M) Politeknik Manufaktur Bandung (Polman Bandung), 2020)
The development of the industrial world regarding electricity supply is in great demand at the moment,converter is used to lower and increase the voltage obtained from the changing input generated during regenerative braking,with a motor made by BLDC as a propulsion owned and then developed by regenerative braking with this regulator compiling the installed input changes can be used to reduce and conquer obtained when regenerative braking is done with output 40 volts, the voltage sensor will be given an output voltage with Arduino as the controller. at an output voltage between 39-40 volts, this voltage can be used to charge the battery.